Limnobaculum parvum gen. nov., sp. nov., isolated from a freshwater lake. Issue 6 (17th April 2019) - Baek, Chaeyun; Shin, Su-Kyoung; Yi, Hana
Abstract : A Gram-stain-negative, rod-shaped, facultatively anaerobic bacterium, designated as strain HYN0051 T, was isolated from lake water. 16S rRNA gene sequence analyses indicated that the isolate shares the highest sequence similarity with the genus Pragia (97.1 %) of the family Enterobacteriaceae . Strain HYN0051 T did not form a rigid clade with the genus Pragia in any of the phylogenetic trees, demonstrating the novel generic status of the isolate. The genome of strain HYN0051 T (CP029185) is a single circular chromosome of 3.84 Mb. The major fatty acids detected were C14 : 0, C16 : 0, summed feature 2 (C12 : 0 aldehyde and/or unknown 10.928), summed feature 3 (C16 : 1 ω6 c and/or C16 : 1 ω7 c ) and summed feature 8 (C18 : 1 ω 6 c and/or C18 : 1 ω 7 c ). The isoprenoid quinones were Q-8, MK-8 and DMK-8. The major polar lipids were phosphatidylglycerol, phosphatidylethanolamine and one unidentified phospholipid. The genome size, G+C content and fatty acid profile were very similar to that of the genus Pragia, but the composition of isoprenoid quinones and polar lipids, and numerous phenotypic properties also supported the distinctiveness of the new isolate from the genus Pragia . Thus, based on phylogenetic and phenotypic data, a novel species of a new genus, Limnobaculum parvum gen. nov., sp. nov., is proposed. The type strain of Limnobaculum parvum is HYN0051 T (=KACC 19186 T =NBRC 112742 T ).